Avascular Necrosis of the Femoral Head. Issue 3 (3rd April 2019) - Seijas, Roberto; Sallent, Andrea; Rivera, Eila; Ares, Oscar
ABSTRACT: About 250000 patients are operated on annually for hip arthroplasty in the USA alone. Of this number, about 10% the cause of their osteoarthritis is the avascular necrosis of the femoral head. But the causes of necrosis are multiple and many of them are still unknown. That is why small advances in etiopathogenesis, diagnosis and treatment of different causes are very important in order to reduce the number of affected patients. It may seem that small changes, studies focused on the details of different diseases do not bring great changes to science, but it is these small changes that end up adding great evolutions in our knowledge. In addition, the changes of recent years, are not focused on our specialty in technical or anatomical evolutions exclusively, but are often based on biological bases, which is the branch that evolves more within trauma and orthopedics. That is why open and constant minds are what help us move forward.